Impacts of different land and water management interventions on runoff and sediment yield under climate change: a case study from the Bale Eco-Region, Ethiopia - Tarkegn, T. G.; Mekuria, Wolde; Ray, R. L.; Tefera, G. W.; van Oel, P. R.; Chukalla, A. D.; Adgo, E.; Worqlul, A. W.; Dile, Y. T.; Seid, Abdulkarim; Bantider, A.; Berhanu, D.; et al. (Informa UK Limited, 2025)
This study evaluated the impacts of land and water management (LWM) intervention scenarios on runoff and sediment yield (SY) in Ethiopia’s Bale Eco-Region (BER) under changing climate conditions. The scenarios analyzed include implementing conservation measures in non-cultivated lands (Scenario 1), cultivated lands (Scenario 2), and a combination of both (Scenario 3). These were compared against a Reference Scenario (i.e., no LWM interventions). The revised Soil and Water Assessment Tool (SWAT+) model was applied for baseline (1992–2020), and midcentury (2041–2070) and late-century (2071–2100) periods under SSP2-4.5 and SSP5-8.5 climate projections. Model calibration (2001–2009) and validation (1995–2000) for streamflow and sediment parameters confirmed SWAT+ suitability for the BER. Results indicate that, under the Reference Scenario, runoff and SY are projected rise by 12.8–53.7% and 16–60.6%, respectively, in future periods. Scenario 3, followed by Scenario 1, provided the greatest reductions in average areal runoff and SY. This study shows that conserving non-cultivated lands through LWM practices significantly reduces runoff and sediment yield. To effectively mitigate these impacts under changing climates, conservation should prioritize both cultivated and non-cultivated lands. The presented framework offers a transferable approach for evaluating LWM strategies in regions with comparable environmental conditions.